Chen System as a Controlled Weather Model Physical Principle, Engineering Design and Real Applications - Pitikhate Sooraksa; Guanrong Chen (My University, 2018)
This paper presents the Chen system as a controlled weather model. Mathematically, the Chen system is dual to the Lorenz system via time reversal. Physically, the Chen system can be viewed as a controlled weather model from the anti-control perspective. This paper illustrates the physical principle of this controlled weather model, and develops an engineering design of the model for real indoor climate (temperature-humidity) regulation, with a perspective on outdoor weather control application.
Keywords: Chen; Weather modification; Chaos control and synchronization